The ring & the crown - De la Cruz, Melissa, 1971- (Hyperion, 2014)
In an alternative past where the Franco-British Empire controls the world's only source of magic, Princess Marie-Victoria, heir to the throne, and Aelwyn Myrddyn, a bastard mage, rekindle their childhood friendship as they plot to save Marie from a loveless, political marriage.